Ellagic acid improved neurodegeneration caused by ischemic stroke through the regulation of glutamatergic and synaptic signaling: Ellagic acid modulates synaptic signaling in stroke (Indian Journal of Experimental Biology (IJEB), 2025)
Ischemic stroke, caused by disrupted cerebral blood flow, leads to neurodegeneration through nutrient and oxygen deprivation. Despite ellagic acid's (EA) known antioxidant/anti-inflammatory roles in stroke, its direct modulation of synaptic NMDA/AMPA receptors remains unexplored. This study investigates EA's neuroprotection via glutamatergic signaling in ischemic stroke in a transient middle cerebral artery occlusion (MCAO) rat model. Wistar rats were divided into sham, MCAO, and EA-treated MCAO groups. Daily EA administration for 72 hours significantly improved neurobehavioral deficits and reduced cerebral edema in MCAO rats (P-value